A field evaluation of a rapid dual immunoassay for human immunodeficiency virus and syphilis antibodies, Hanoi, Vietnam. (February 2019) - Withers, Keenan; Bristow, Clare; Nguyen, Minh; Stafylis, Chrysovalantis; Giang, Le M; Klausner, Jeffrey D
The SD BIOLINE HIV/Syphilis Duo (SD BIOLINE DUO) rapid test is a dual rapid lateral flow immunoassay that detects antibodies to both human immunodeficiency virus (HIV) and Treponema pallidum (TP) 'syphilis' via fingerprick whole blood. We evaluated the field performance of the SD BIOLINE HIV/Syphilis Duo test among two populations in Hanoi, Vietnam – men who have sex with men (MSM) and pregnant women. We also surveyed factors that influence participants' willingness to test for HIV and syphilis. This test has the potential to increase HIV and syphilis screening in low-resource settings. Patients who received healthcare services at a sexual health clinic for MSM and a district antenatal care center in Hanoi, Vietnam were recruited for the study. Participants with HIV and syphilis were intentionally recruited for adequate test performance evaluation via convenience sampling. At each facility, venipuncture blood specimens were obtained for reference testing for HIV and TP using SD BIOLINE HIV 1/2 3.0 and TP particle agglutination, respectively. SD BIOLINE DUO was compared to the standard reference tests and sensitivity and specificity were calculated. We calculated 95% confidence interval (CI) using the exact binomial method. We used conjoint analysis to identify test attributes that are associated with participant likelihood to seek HIV and syphilis testing. Of 280 participants, 100 (35.7%) were MSM and 180 (64.3%) were pregnant women. Of MSM, 17 (17.0%) were HIV positive and 49 (49.0%) were TP seropositive. All women were negative for both HIV and syphilis antibodies. For HIV antibody testing, sensitivity and specificity were 100.0% (95% CI: 80.5–100.0%) and 100.0% (95% CI: 98.6–100.0%), respectively. For the syphilis antibody testing, sensitivity and specificity were 83.1% (95% CI: 71.0–91.6%) and 100.0% (95% CI: 98.3–100.0%), respectively. Potential for false positives, preference for one blood draw over two, and shorter wait time for testing results were the highest ranked attributes by participants according to their willingness to test. The SD BIOLINE HIV/Syphilis Duo rapid test demonstrated very good performance in this field setting and participants preferred attributes that aligned well with this test.